The Role of the Third Acid-Fast Bacillus Smear in Tuberculosis Screening for Infection Control Purposes: A Controversial Topic Revisited. Issue 1 (2011) - Wilmer, A.; Bryce, E.; Grant, J.
Abstract : INTRODUCTION: Recent studies have suggested that two negative acid-fast bacillus (AFB) smears may be as effective as three when screening patients with suspected Mycobacterium tuberculosis for respiratory isolation purposes. However, current recommendations in Canada, the United States and Europe still support a three-smear approach. METHODS: The microbiology database of a tertiary care hospital was searched for sputum, tracheal aspirates and bronchoalveolar lavage samples from 2003 to 2007 that had been sent for mycobacterial testing. The first patient specimen to become AFB smear positive was noted. As well, the time required to collect the third specimen in hospitalized patients who remained smear negative was used to estimate the savings in isolation costs associated with a two-smear approach. RESULTS: There were 8347 respiratory specimens from 5168 patients in the five-year period. Of these patients, 2.2% (116 of 5168) were AFB smear positive, of whom 55.2% (64 of 116) were culture positive for Mycobacterium tuberculosis . Overall 89% (57 of 64) of patients were identified as being AFB smear positive by the first smear, 7.8% (five of 64) were identified by the second smear and 3.2% (two of 64) were identified by further smears. Smear-negative patients spent a combined 710 days in isolation awaiting collection of the third sample at a cost of approximately 142, 000 over five years. CONCLUSION: A two-smear approach for discontinuation of respiratory isolation precautions is safe and has the potential to reduce hospital expenditures.